Study on the optimal elastic modulus of flexible blades for right heart assist device supporting patients with single-ventricle physiologies - Chen, Tong; Cheng, Xiaoming; Liu, Xudong; Zhang, Huifeng; Wang, Shengzhang (Frontiers in Cardiovascular Medicine, 2024)
Background: Patients with single-ventricle physiologies continue to experience insufficient circulatory power after undergoing palliative surgeries. This paper proposed a right heart assist device equipped with flexible blades to provide circulatory assistance for these patients. The optimal elastic modulus of the flexible blades was investigated through numerical simulation.Methods: A one-way fluid-structure interaction (FSI) simulation was employed to study the deformation of flexible blades during rotation and its impact on device performance. The process began with a computational fluid dynamics (CFD) simulation to calculate the blood pressure rise and the pressure on the blades' surface. Subsequently, these pressure data were exported for finite element analysis (FEA) to compute the deformation of the blades. The fluid domain was then recreated based on the deformed blades' shape. Iterative CFD and FEA simulations were performed until both the blood pressure rise and the blades' shape stabilized. The blood pressure rise, hemolysis risk, and thrombosis risk corresponding to blades with different elastic moduli were exhaustively evaluated to determine the optimal elastic modulus.Results: Except for the case at 8000 rpm with a blade elastic modulus of 40 MPa, the pressure rise associated with flexible blades within the studied range (rotational speeds of 4000 rpm and 8000 rpm, elastic modulus between 10 MPa and 200 MPa) was lower than that of rigid blades. It was observed that the pressure rise corresponding to flexible blades increased as the elastic modulus increased. Additionally, no significant difference was found in the hemolysis risk and thrombus risk between flexible blades of various elastic moduli and rigid blades.Conclusion: Except for one specific case, deformation of the flexible blades within the studied range led to a decrease in the impeller's functionality. Notably, rotational speed had a more significant impact on hemolysis risk and thrombus risk compared to blade deformation. After a comprehensive analysis of blade compressibility, blood pressure rise, hemolysis risk, and thrombus risk, the optimal elastic modulus for the flexible blades was determined to be between 40 MPa and 50 MPa.